2017
DOI: 10.1016/j.addbeh.2016.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Early life predictors of alcohol-related attitudes among 11-year-old never drinkers

Abstract: Alcohol-related attitudes are evident before children have personal experience drinking alcohol and represent key proximal predictors of alcohol use, but relatively little is known about how early life characteristics predict these attitudes. Among late childhood lifetime alcohol abstainers (Mage=10.67 years; 51% girls), we examine predictors of positive alcohol expectancies and perceived risk of alcohol use. Data from the Millennium Cohort Study, an ongoing nationally representative longitudinal study of chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…These studies were limited by a reliance on retrospective recollection of alcohol consumption for both minors and their parents [80, 81, 87, 93, 94, 97, 102, 107, 108]. Some studies were further limited by requiring children to report on both their own and their parents' alcohol use [86, 88–90, 96–98, 101].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies were limited by a reliance on retrospective recollection of alcohol consumption for both minors and their parents [80, 81, 87, 93, 94, 97, 102, 107, 108]. Some studies were further limited by requiring children to report on both their own and their parents' alcohol use [86, 88–90, 96–98, 101].…”
Section: Resultsmentioning
confidence: 99%
“…The relevant research in this area examined: (i) how parental alcohol intake is associated with adverse alcohol-related outcomes in children (28 articles identified); and (ii) how children's observation of parental alcohol consumption affects children's attitudes and beliefs (4 articles). While research relevant to the first area does not directly examine exposure to alcohol consumption behaviours, it is acknowledged in the literature that greater parental alcohol use is likely to result in their children witnessing more alcohol consumption [29,46,[79][80][81][82]. Therefore, in line with research in the area and for the purposes of this review, greater parental consumption was considered a proxy for increased exposure to parental drinking behaviours.…”
Section: Exposure To Parents Consuming Alcoholmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies found that while African-American youth initially had higher positive alcohol expectancies relative to White youth, more positive alcohol expectancies were only predictive of alcohol use in White youth [ 12 , 13 ]. However, another study in the United Kingdom found that White British children had higher positive alcohol expectancies than Black and Asian British children [ 14 ]. Several studies have found that older age is associated with higher positive expectancies [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%